EXPLORING TEACHERS’ PERSPECTIVES ON THE CONSTRUCTIVE IMPACTS OF MICROLEARNING TIKTOK IN ASSESSING STUDENTS’ SPEAKING SKILL - Utami, Ni Luh Kadek Mega; Saroh, Yam (Yavana Bhasha : Journal of English Language Education, 2025)
Merdeka Curriculum frees teachers and students to use any learning media during the learning process. Thus, teachers can select any teaching media and tools to assist students learn in the classroom. Considering that perspective, the focus of this study is to unveil the constructive impacts experienced by teachers when using TikTok as an assessment tool to evaluate students’ speaking skills. This study employs a qualitative exploratory design. The data were obtained through observation, an E-questionnaire, and an in-depth interview with three English teachers of senior high schools in Denpasar, Bali as the participants. The participants were chosen by using a purposive sampling technique. The data collection period spanned two months. The findings showed the constructive impacts of TikTok as a speaking assessment could increase the students’ speaking skills, covering five aspects (vocabulary, grammar, pronunciation, fluency, and comprehension). The results highlight that TikTok can not only be used as a learning media but also be used as an assessment tool. Teachers found that TikTok was a practical digital platform for students to perform their speaking skills where they practiced using short videos, a compact content encouraging them to speak more freely and helping the teachers assess their speaking skills.   Keywords: Constructive Impacts; Microlearning; Speaking Assessment; TikTok Application.